2006
DOI: 10.1530/eje.1.02173
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic abnormalities in patients with normocalcemic hyperparathyroidism detected at a population-based screening

Abstract: Objective: Dyslipidemia, hypertension, diabetes mellitus and also primary hyperparathyroidism (pHPT) are associated with an increased risk of cardiovascular diseases. Metabolic abnormalities in mild pHPT have been reported, but never in cases with normal calcium and high parathyroid hormone (PTH) levels, i.e. suffering from 'normocalcemic pHPT'. Our aim was to explore the occurrence of these metabolic abnormalities in individuals with normocalcemic pHPT identified in a population-based screening, and the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
64
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(73 citation statements)
references
References 44 publications
5
64
0
4
Order By: Relevance
“…19,20 Individuals with normocalcemic hyperparathyroidism have been shown to have increased BMI, triglycerides, LDL cholesterol and blood glucose. 21 Our findings confirm the relationships between PTH and BMI, fat mass, blood pressure and lipid levels, and also highlight an association between PTH and coronary artery calcification that has not, to our knowledge, been previously reported. Associations between PTH and cardiometabolic risk factors were present throughout the entire cohort, indicating that this relationship is not unique to those with the highest PTH levels.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…19,20 Individuals with normocalcemic hyperparathyroidism have been shown to have increased BMI, triglycerides, LDL cholesterol and blood glucose. 21 Our findings confirm the relationships between PTH and BMI, fat mass, blood pressure and lipid levels, and also highlight an association between PTH and coronary artery calcification that has not, to our knowledge, been previously reported. Associations between PTH and cardiometabolic risk factors were present throughout the entire cohort, indicating that this relationship is not unique to those with the highest PTH levels.…”
Section: Discussionsupporting
confidence: 90%
“…36,37 To our knowledge, no studies have documented reductions in weight, cardiovascular events or mortality following parathyroidectomy for primary hyperparathyroidism. 21 On the other hand, if cardiometabolic risk influences PTH, then PTH concentrations would be expected to mimic fluctuations in cardiovascular and metabolic parameters. Previous work by our group suggests that weight gain predates PTH elevation in women with primary hyperparathyroidism, 38 and a study in obese adolescents found that PTH decreased significantly following weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, these findings support a risk for cardiovascular morbidity and mortality in low-risk asymptomatic PHPT at least not lower than in symptomatic PHPT [2,3,12]. Consistently, also normocalcemic PHPT has been associated to metabolic and cardiovascular abnormalities [26,27]. These data are in line with recent consideration of MacFarlane et al [28] who suggest that "mild PHPT," that commonly refers to individuals not meeting the NIH criteria for parathyroidectomy, should be reclassified as an insidious disease.…”
Section: Discussionmentioning
confidence: 78%
“…It has been argued that the excess mortality seen among patients with PHPT belongs to the era of severe symptomatic disease, whereas nowadays the disease is mostly recognized in a mild asymptomatic state characterized by lower serum calcium concentrations (2,7). Although there is some suggestion that the degree of hypercalcemia is directly correlated with the increased CV risk (8), an atherogenic metabolic profile has been reported in patients with normocalcemic (NC)-PHPT (9). The issue is further compounded by the lack of agreement in the literature over the possible amelioration of metabolic parameters, or the putative reversibility of hypertension and myocardial hypertrophy following successful surgery (2,10).…”
Section: Introductionmentioning
confidence: 99%